Investigation of Traffic Loading Effects for Different Codes on Medium- and Small-Span Girder Bridges in China - Qingfei Gao; Biao Wu; Jun Li; Kemeng Cui; Chuang Xu (Advances in Civil Engineering)
With increasing traffic volume, the traffic load grade given by design codes has gradually increased. For new bridges, there is no problem, and the traffic load can be met through the requirements of the new code. However, for existing bridges, there is a lack of uniform standards on whether they can continue to be used. It is not clear whether these bridges will be judged according to the new code or the original design code. The traffic loading effects of different codes on medium- and small-span girder bridges in China are investigated in this study. Three codes are introduced: JTJ 021-89, JTG D60-2004, and JTG D60-2015. Simply supported girder bridges and continuous girder bridges are discussed. The traffic loading effects calculated based on JTG D60-2015 are significantly larger than those calculated based on JTJ 021-89. For simply supported girder bridges, most of the differences range from 20% to 40%, and the maximum value is almost larger than 60%. For continuous girder bridges, most of the differences in the positive bending moments are concentrated in the 20%∼40% range, while the differences in the negative bending moments range from 10% to 20%. Therefore, the differences in traffic loading effects calculated based on various codes cannot be ignored in actual bridge engineering. The conclusion in this study can provide a basis for bridge structure evaluation and life prediction.